Design of the Manakarra Stadium area as an integrated disaster evacuation facility to reduce disaster risk in Mamuju Regency, West Sulawesi - Arwansyah, Arwansyah; Chaerul, Muhammad; Gusty, Sri (Universitas Ibn Khaldun Bogor, 2025)
Mamuju Regency, located in West Sulawesi, is a region highly vulnerable to various types of natural disasters, including earthquakes, floods, and landslides. However, following the earthquakes in January and June 2021, the use of Manakarra Stadium as a gathering point for evacuees revealed significant social issues due to the poorly organized placement of facilities. In this context, Manakarra Stadium is being proposed as an integrated disaster evacuation facility, serving not only as a sports venue but also as a center for protection and recovery for the community. This study aims to design Manakarra Stadium as an effective and efficient evacuation facility in the context of disaster risk reduction. Utilizing a data-driven approach and community needs analysis, the proposed design is expected to make a significant contribution to enhancing disaster resilience in the region. The design of this evacuation facility at Manakarra Stadium could serve as a model for both government and community disaster responses in the aftermath of future events.